ANALISIS PENGHINDARAN RISIKO PADA KEPUTUSAN INVESTASI DI PASAR MODAL INDONESIA - Tazkiyah Sakinah; Budi Purwanto; Wita Juwita Ermawati (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Decision making in the capital market is not always rational. It is due to the emotional involvement of investors, which is described through financial behavior. Investor decision making based on financial behavior is considered as a loss aversion contained in prospect theory. In this theory, the prospect of risk aversion behavior when the market is profitable, but this behavior becomes an obstacle for investors to get higher returns. This study aimed to analyze the risk avoidance behavior that limits investment decision making in Indonesian stock investors. Primary data were obtained from individual investor transactions on the IDX, and secondary data were in the form of daily stock data. Identification of risk aversion was carried out using a non-linear regression method. The measurement of psychological resistance was carried out through an independent sample t-test by measuring the difference between actual and expected returns. The results showed that Indonesia's capital market investors have a risk-averse behavior in the gain domain and risk-seeking in the loss domain. Risk-averse behavior could reduce investment productivity. Keywords: behavioral finance, decision-making, prospect theory, return, risk averse